2018
DOI: 10.3389/fchem.2018.00411
|View full text |Cite
|
Sign up to set email alerts
|

Light-Mediated Growth of Noble Metal Nanostructures (Au, Ag, Cu, Pt, Pd, Ru, Ir, Rh) From Micro- and Nanoscale ZnO Tetrapodal Backbones

Abstract: Micro- and nanoscale ZnO tetrapods provide an attractive support for metallic nanostructures since they can be inexpensively produced using the flame transport method and nanoparticle synthesis schemes can take advantage of a coupled response facilitated by the formation of a semiconductor-metal interface. Here, we present a light-mediated solution-based growth mode capable of decorating the surface of ZnO tetrapods with nanostructures of gold, silver, copper, platinum, palladium, ruthenium, iridium, and rhodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Alteration of photocatalytic properties may be achieved using different synthesis methods [1,18,19], which convey various morphologies of ZnO NPs, such as rods, spheres, tubes and others, with particle size as small as 2-10 nm [20][21][22][23]. However, care must be taken about the cost, complexity, feasibility and toxicity of the method opted for synthesis [24]. Ni et al [22] have demonstrated a cost-effective and simple hydrothermal process for the synthesis of ZnO nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of photocatalytic properties may be achieved using different synthesis methods [1,18,19], which convey various morphologies of ZnO NPs, such as rods, spheres, tubes and others, with particle size as small as 2-10 nm [20][21][22][23]. However, care must be taken about the cost, complexity, feasibility and toxicity of the method opted for synthesis [24]. Ni et al [22] have demonstrated a cost-effective and simple hydrothermal process for the synthesis of ZnO nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the aforementioned drawbacks, a workable solution to improve the optical absorption capacity and reduce charge recombination of ZnO is desired. It is well known that noble metals have desirable properties, such as surface plasmon resonance, straightforward reduction, chemical stability and bio-affinity 1620 . Among them, Au nanoparticles show excellent SPR properties and charge storage capability 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Until now, possible solutions have been tested. Metals doping (such as gold, silver, rhodium, or platinum) [22,23], metal ions doping (such as Bi or Al) [24], and nitrogen doping [25] are the most used techniques to give rise to visible light activity of the semiconductor materials, to extend their light absorption ability from UV to visible range and to feature good electron transport. Beyond that, heterojunctions, which can effectively capture the photo-generated charge carriers to improve the charge separation efficiency, decrease the surface reaction over potential, enhance apparent quantum efficiencies and provide active sites for surface redox reaction at two different reaction sites, are believed to be essential to achieving highly efficient photocatalytic performances [26,27,28,29,30,31,32,33,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%